Pengembangan Website Informasi Rumah Koding Mafaza untuk Anak Usia Dini dan Sekolah Dasar - Najla Nafila; Fero Triando; Muhammad Fikri (Universitas Ngudi Waluyo, 2026)
This study aims to develop an informational website for Rumah Koding Mafaza as a non-formal educational institution serving early childhood and elementary school students. The website is designed to function as a centralized medium for information dissemination and institutional promotion rather than as an online learning platform. The research employed a Research and Development (R&D) approach with the Rapid Application Development (RAD) model to enable fast and iterative system development. Data were collected through observation, interviews, documentation, and literature studies to identify institutional needs and system requirements. The development stages included needs analysis, system design, implementation using the Laravel framework, and limited testing. The results show that the developed website successfully provides structured information on institutional profiles, learning programs, class schedules, activity documentation, and online registration access through Google Forms. The website improves information accessibility, enhances institutional credibility, and supports more efficient communication between the institution and parents. This study contributes to the development of simple and effective web-based information systems for non-formal education institutions serving children. Abstrak Penelitian ini bertujuan untuk mengembangkan website informasi Rumah Koding Mafaza sebagai lembaga pendidikan nonformal yang melayani anak usia dini dan sekolah dasar. Website ini dirancang sebagai media informasi dan promosi yang terpusat, bukan sebagai platform pembelajaran daring. Metode penelitian yang digunakan adalah Research and Development (R&D) dengan pendekatan Rapid Application Development (RAD) agar proses pengembangan sistem dapat dilakukan secara cepat dan iteratif. Teknik pengumpulan data meliputi observasi, wawancara, dokumentasi, dan studi literatur untuk mengidentifikasi kebutuhan lembaga dan sistem. Tahapan pengembangan meliputi analisis kebutuhan, perancangan sistem, implementasi website menggunakan framework Laravel, serta pengujian terbatas. Hasil penelitian menunjukkan bahwa website yang dikembangkan mampu menyediakan informasi lembaga secara terstruktur, meliputi profil lembaga, program pembelajaran, jadwal kelas, dokumentasi kegiatan, serta akses pendaftaran online melalui Google Form. Website ini meningkatkan kemudahan akses informasi, memperkuat citra profesional lembaga, serta membantu orang tua dalam memperoleh informasi tanpa harus berkomunikasi langsung dengan admin.